Restriction endonuclease banding for cytogenetic characterization of fishes - Nagpure, N S; Srivastava, K Satish; Kushwaha, B (Indian Journal of Fisheries, 2011)
Fixed chromosomes of Indian major carps Labeo rohita (Ham.), Catla catla (Ham.) and Cirrhinus mrigala (Ham.) were digested with restriction enzyme (RE) Bam HI. The RE induced serial G-like bands on chromosomes of IMCs, which varied between the species. In Labeo rohita the banding pattern was more crisp and clear than C. catla and C.mrigala. The results indicated that, in addition to conventional banding techniques, RE banding could be used for cytogenetic characterization of fish species.